Model of Transformational Leadership, Risk Management Factors Influencing on Law Performance - Zaher Omair Juma, Abdulla Ahmed; A. Perumal, Puvanasvaran; Mansoor, Nusaibah (International Journal of Sustainable Construction Engineering and Technology, 2022)
The ability of law enforcement organisations to effectively combat crime depends on their use of innovation and workplace transformation. When the need for change in law enforcement organisations’ daily operations becomes more and more apparent, transformational leadership has been shown to be extremely beneficial in risk management and enhancing police performance. The right strategy for effective policing development and improving police officer performance is established by this leadership style. The Dubai Police Department’s performance in enforcing the law suffers in the absence of effective risk management and transformational leadership, potentially jeopardising the relationship between officers and all departments. As a result, this study created a model outlining the causal links between risk management and transformational leadership and the effectiveness of law enforcement. This study was quantitatively conducted, collecting 381 completed responses that were statistically analysed using SPSS and AMOS. The responses gathered during the data collection process were verified by the reliability analysis. Using fit index parameters to define the relationship between risk management and transformational leadership and law enforcement performance, AMOS analysis revealed that the developed model is satisfactory. The police department will be able to effectively manage risk with the help of this finding in order to reduce crime and create a security plan for the officers.